1999
DOI: 10.1128/jvi.73.8.6430-6435.1999
|View full text |Cite
|
Sign up to set email alerts
|

Both Memory and CD45RA+/CD62L+Naive CD4+T Cells Are Infected in Human Immunodeficiency Virus Type 1-Infected Individuals

Abstract: Cellular activation is critical for the propagation of human immunodeficiency virus type 1 (HIV-1) infection. It has been suggested that truly naive CD4+ T cells are resistant to productive HIV-1 infection because of their constitutive resting state. Memory and naive CD4+ T-cell subsets from 11 HIV-1-infected individuals were isolated ex vivo by a combination of magnetic bead depletion and fluorescence-activated cell sorting techniques with stringent criteria of combined expression of CD45RA and CD62L to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(61 citation statements)
references
References 37 publications
(59 reference statements)
3
57
0
Order By: Relevance
“…Moreover, our previous studies have revealed no absolute restriction to HIV-1 infection, replication, or depletion of T cells within these cultures on the basis of target cell maturation or proliferation (47). In particular, these studies demonstrated de novo infection and depletion of resting, naive lymphocytes, which may explain the observation of productively infected resting T cells in vivo (50)(51)(52). Because these cells divide very infrequently (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, our previous studies have revealed no absolute restriction to HIV-1 infection, replication, or depletion of T cells within these cultures on the basis of target cell maturation or proliferation (47). In particular, these studies demonstrated de novo infection and depletion of resting, naive lymphocytes, which may explain the observation of productively infected resting T cells in vivo (50)(51)(52). Because these cells divide very infrequently (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The inhibition of HIV-1 replication by CD38 expression may account for the lower susceptibility of resting/ naive (CD45RA ϩ ) than memory (CD45R0 ϩ ) CD4 ϩ T cells (47)(48)(49), since resting naive cells constitutively express CD38, whereas resting memory cells are CD38 Ϫ (16). Moreover, it may play a role in the favorable prognostic value of high levels of CD38 on CD4 ϩ cells in HIV ϩ children (26) and in the relative resistance to HIV-1 infection shown by children born to a Cells were stained with FITC-conjugated gp120.…”
Section: Discussionmentioning
confidence: 99%
“…Replication competent HIV-1 particles were recovered after optimal non-specific activation from each of these T-lymphocyte subsets. A simultaneous study also demonstrated integrated proviral DNA in naive CD4+ CD45RA+ CD62L+ T-cells (38). The presence of integrated provirus in naive lymphocytes may result from the infection of activated thymocytes (7), from the reversion toward a naive phenotype of latently infected memory Tcells (36) or from their direct infection (43).…”
Section: Viral Integration In Subsets Of Lymphocytesmentioning
confidence: 94%